PENGEMBANGAN MODUL PRAKTIKUM KIMIA BERBASIS POE (PREDICT-OBSERVE-EXPLAIN) PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Dyan Eka Tamara; Kuntum Khaira; Dona Afriyani; Maya Sari (Journal of Chemistry Education and Integration, 2022)
This research is motivated by the main problem in this thesis is the unavailability of the Chemistry Practicum Module at SMAN 2 Padang Panjang. The purpose of this research is to find out the validity and practicality of the development of POE-based chemical practicum modules (Predict-Observe-Explain) in order to help learners in implementing of the practicum process implemented at SMAN 2 Padang Panjang to manifest learning in the form of practicum runs smoothly and has clear guidelines. The research method that used by the researcher is a research and development method by developing a 4-D Learning Model (define, design, develop, and disseminate). But in this study only reached the stage of development (develop) due to time constraints. Product eligibility is done by validating the validator. Then, the researcher conducted practicality tests on learners in class X Mipa I SMAN 2 Padang Panjang. Based on the results of product validation, a percentage of 87.97% was obtained with very valid criteria, and the practical percentage of POE-based Chemical Practicum Module (Predict-Observe-Explain) as seen from the results of the student questionnaire of 86.23%.Keywords : Practicum, POE, Electrolyte and Non-Electrolyte